Second‐line chemotherapy for advanced biliary tract cancer after failure of the gemcitabine‐platinum combination: A large multicenter study by the Association des Gastro‐Entérologues Oncologues. Issue 18 (5th June 2015) - Brieau, Bertrand; Dahan, Laetitia; De Rycke, Yann; Boussaha, Tarek; Vasseur, Philippe; Tougeron, David; Lecomte, Thierry; Coriat, Romain; Bachet, Jean‐Baptiste; Claudez, Pierre; Zaanan, Aziz; Soibinet, Pauline; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Few data are available on second‐line chemotherapy (CT2) for advanced biliary tract cancer (ABTC). The aim of this multicenter study was to describe the CT2 regimens used, the response rates, and the outcomes of patients treated with various CT2 regimens. METHODS Patients who received CT2 for ABTC at 17 French institutions after the failure of the gemcitabine‐platinum combination were retrospectively studied. Progression‐free survival (PFS) and overall survival (OS) were estimated with the Kaplan‐Meier method. Cox models were used for multivariate analyses. RESULTS Among 603 patients who received first‐line chemotherapy (CT1) for ABTC, 196 received CT2: 5‐fluorouracil (5‐FU) and irinotecan (n = 64), 5‐FU and oxaliplatin (n = 21), 5‐FU and cisplatin (n = 38), 5‐FU or capecitabine (n = 40), sunitinib (n = 10), or other various regimens (n = 23). Among the 186 assessable patients, there were 22 partial responses and 70 stabilizations. After a median follow‐up of 26.4 months, the median PFS and OS were 3.2 and 6.7 months, respectively. There was no significant difference in PFS or OS between CT2 regimens. Fluoropyrimidine‐based doublet chemotherapy was not superior to fluoropyrimidine alone in terms of OS and PFS. In a multivariate analysis, a performance status of 0 to 1, disease control with CT1, and a carbohydrate antigen 19‐9 (CA 19‐9) level ≤ 400 IU/mL were significantly associated with longer PFS and OS. Grade 3 to 4 toxicity occurred in 32% of the patients. CONCLUSIONS CT2 might provide disease control for selected patients with ABTC after the failure of gemcitabine‐platinum, but the prognosis remains poor. No particular regimen seems superior to others, and this calls for new treatments. A good performance status, disease control with CT1, and a low level of CA 19‐9 were associated with longer survival. Cancer 2015;121:3290–3297. © 2015 American Cancer Society.